1991
DOI: 10.1116/1.577220
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated evaporation of SiO2 and Si3N4 films by synchrotron radiation and its application for low-temperature cleaning of Si surfaces

Abstract: Articles you may be interested inEtching of SiO 2 film by synchrotron radiation in hydrogen and its application to lowtemperature surface cleaning Role of surface adsorption in the surfaceinduced alignment of nematic liquid crystals on evaporated SiO films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Although we do not discuss the etching mechanisms in this work, the high spatial resolution, anisotropic and high-speed etching at room temperature indicates that the etching is induced by the electronic excitation of PDMS (Urisu & Kyuragi, 1987;Streller et al, 1998;Akazawa et al, 1991). The extremely high etching rate, 40-50 mm (10 min)…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation
“…Although we do not discuss the etching mechanisms in this work, the high spatial resolution, anisotropic and high-speed etching at room temperature indicates that the etching is induced by the electronic excitation of PDMS (Urisu & Kyuragi, 1987;Streller et al, 1998;Akazawa et al, 1991). The extremely high etching rate, 40-50 mm (10 min)…”
Section: Figurementioning
confidence: 92%
“…The synchrotron radiation (SR) stimulated etching process (Urisu & Kyuragi, 1987;Streller et al, 1998;Akazawa et al, 1991;Wen & Chou, 2000;Nonogaki et al, 2000;Wang et al, 2006) has many unique features, such as selective cleaving of chemical bonds by exciting certain dissociative energy levels, low damage to substrates in comparison with the plasma process, high material selectivity, anisotropic etching, lowering of the process temperature, and high spatial resolution and aspect ratio because of the short wavelengths. Although a large number of studies have been reported on SR etching on solid materials, there are no studies reporting the SR process on elastic materials to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, in previous studies using synchrotron radiation, direct etching at room temperature proved impossible, and it was necessary either to heat the workpiece [14-16, 19, 21] or to use reactive gases [12,17,18,20,22]. In the former case, the etching rate improves as the temperature is raised to about 700 °C [16,19,21]. Thus, etching of SiO 2 and Si is possible using synchrotron radiation.…”
Section: Micromachining Of Transparent Materialsmentioning
confidence: 96%
“…However, in the previous studies using synchrotron radiation, direct etching at room temperature proved impossible; it was necessary either to heat up the workpiece [14-16, 19, 21], or to use reactive gases [12,17,18,20,22]. In the former case, the etching rate improves as the temperature is raised up to about 700 °C [16,19,21], and an activation energy of 0.7 eV is needed [21]. The etching rate of SiO 2 is more than an order of magnitude lower than that of Si [24], and therefore crystalline Si can be used as a mask for SiO 2 etching [19,21].…”
Section: Introductionmentioning
confidence: 97%
“…In the former case, the etching rate improves as the temperature is raised up to about 700 °C [16,19,21], and an activation energy of 0.7 eV is needed [21]. The etching rate of SiO 2 is more than an order of magnitude lower than that of Si [24], and therefore crystalline Si can be used as a mask for SiO 2 etching [19,21]. On the other hand, SiO 2 can be etched even at room temperature if synchrotron light is applied in an atmosphere of SF 6 or some other reactive gas.…”
Section: Introductionmentioning
confidence: 98%